Operative methods for delayed paralysis after osteoporotic vertebral fracture. (5th July 2017) - Kanchiku, Tsukasa; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Nishida, Norihiro; Funaba, Masahiro; Taguchi, Toshihiko
Purpose: How to select operative methods for delayed paralysis after osteoporotic vertebral fracture remains a matter of debate. It is unclear which procedure provides better neurological and functional recovery. This study aimed to compare the various operative methods and investigate postoperative outcomes. Methods: The study included 42 delayed paralysis patients (mean age 73.7 years). The operative methods were posterior spinal shortening osteotomy with direct decompression and short or long fusion and posterior laminectomy and short fusion with vertebroplasty. All patients in the vertebroplasty group were fitted with hooks to prevent correction loss. We investigated postoperative complications, surgery time, intraoperative blood loss, and changes in walking ability and local kyphotic angle (LKA). Patients were divided into three groups: shortening with a peripheral fusion range of one intervertebral level (the SS group, n = 18), the same procedure with a peripheral fusion range of ≥2 intervertebral levels (the SL group, n = 12), and posterior laminectomy and short fusion with vertebroplasty (the VP group, n = 12). Results: Postoperative complications were observed in five patients, all of whom were in the SS and SL group. There were no significant differences between the SS and SL groups. The VP group experienced significantly shorter mean surgery times, significantly lower mean intraoperative blood loss, and an improvement in paralysis, walking ability, LKA, and correction loss. Overall, the VP group had significantly better outcomes. Conclusion: Posterior laminectomy and short fusion with vertebroplasty with the addition of hooks is useful in cases of delayed paralysis in elderly patients.